Hospitalization risk factors of older cohorts of home health care patients: A systematic review. Issue 3 (3rd July 2019) - Bick, Irene; Dowding, Dawn
ABSTRACT: Nearly one million Medicare home health care beneficiaries are hospitalized annually of which one-quarter are considered preventable. Older hospitalized patients are at risk for nosocomial complications and poorer outcomes and incur higher health care costs. This paper reports the results of a systematic review of 28 studies on hospitalization risk factors of older home health care patients. It found that males, Blacks, and non-Asian minorities are at greater hospitalization risk. Factors associated with higher risk included skin ulcers, psychiatric conditions, dyspnea/COPD, cardiovascular conditions, diabetes, functional deficits, more comorbidities, and higher medication usage. These findings can inform practice, research, and policy.